(untitled) (Medical Forum Monthly, 2024)
Objective: .This study was planned to compare and correlate the potential role of resistin in obese patients with T2DM and obese non-diabetic controls and also to evaluate the correlation between resistin and marker of obesity and lipid profile. Study Design: Comparative study Place and Duration of Study: This study was conducted at the Department of Medicine at Lahore General Hospital; Lahore affiliated with Postgraduate Medical Institute, Lahore from January 2016 to March 2017. Materials and Methods: This study was conducted in Physiology Department of Postgraduate Medical Institute Lahore. In this study we also collaborate with Medicine department of General Hospital of Lahore. In this study we had taken 80 (Eighty) male and female obese patients. The patients have not taken any medicine during study. We have not considered pregnant women. The range of age was thirty to fifty five (35 to 55) years. Results: In type 2 diabetic patients we found high level of Serum resistin i.e (38±8 ng/ml) as compare to controls. Serum cholesterol (208 ± 70 mg/dl), serum triglycerides(188 ± 74 mg/dl), serum LDL(160 ± 37 mg/dl) was significantly higher in diabetic obese Patients. Serum HDL (38 ± 15) mg/dl) was significantly low in diabetic subjects. Pearson’s analysis revealed significant correlation between serum resistin and serum triglycerides in both groups. A negative correlation was seen between serum resistin and serum HDL in both groups. Conclusion: Resistin may have a role in disrupting lipid parameters thus leading to insulin resistance in diabetes mellitus in obese subjects